2019
DOI: 10.1001/jamanetworkopen.2019.11895
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Protein p53 and Ataxia-Telangiectasia Mutated Comutation With Response to Immune Checkpoint Inhibitors and Mortality in Patients With Non–Small Cell Lung Cancer

Abstract: This cohort study examines the association of comutation of tumor protein p53 (TP53) and ataxia-telangiectasia mutated (ATM) genes with response to immune checkpoint inhibitor (ICI) treatment and overall survival among patients with non–small cell lung cancer (NSCLC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…TMB has emerged as a predictive biomarker in immunotherapy response across many tumor types including HNSCC [9] . NGS studies have shown a clear association between TP53 mutated tumors with high TMB levels and robust clinical benefit from ICIs in NSCLC [ 47 , 48 ]. In this direction, we evaluated the association between TP53 mutation status, TMB score and overall survival in primary and metastatic (lung and liver) HNSCC tumors of patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…TMB has emerged as a predictive biomarker in immunotherapy response across many tumor types including HNSCC [9] . NGS studies have shown a clear association between TP53 mutated tumors with high TMB levels and robust clinical benefit from ICIs in NSCLC [ 47 , 48 ]. In this direction, we evaluated the association between TP53 mutation status, TMB score and overall survival in primary and metastatic (lung and liver) HNSCC tumors of patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of p53 status on PARP inhibitor sensitivity requires further clarification. Although co-mutation of both ATM and TP53 is rare [59], co-mutation has been shown to occur in 2-3% of non-small cell lung cancer where it increases tumour mutation burden and correlates with better response to immune checkpoint therapy [60], suggesting additional opportunities for targeted therapy for ATM-deficient tumours.…”
Section: Targeting Atm-deficient Cancersmentioning
confidence: 99%
“…P53, mutated in PLC, is a pivotal tumor suppressor gene and a signi cant mainstay in our body's natural anti-cancer defense [66]. Several studies have shown that P53 in liver cancer can function to restrain tumor development [67,68].…”
Section: Discussionmentioning
confidence: 99%